Reclaimed and Up‐Cycled Cathodes for Lithium‐Ion Batteries (Global Challenges 12/2022). Issue 12 (14th December 2022) - Gastol, Dominika; Marshall, Jean; Cooper, Elizabeth; Mitchell, Claire; Burnett, David; Song, Tengfei; Sommerville, Roberto; Middleton, Bethany; Crozier, Mickey; Smith, Robert; Haig, Sam; McElroy, Con Robert; et al.
Abstract : In article 2200046, Dominika Gastol, Emma Kendrick, and co‐workers recover black mass containing mixed LiMn2 O4 and Ni0.8 Co0.15 Al0.05 O2 from a Nissan Leaf pouch cell via two different recycling routes, shredding or disassembly. The reclaimed material is further treated to reclaim the transition metals salts. Upcycled LiNi0.6 Mn0.2 Co0.2 O2 (NMC 622) is produced. The energy inputs of the processing, purity, and performance of the NMC 622 from the two processes are evaluated.